Metal–Organic Framework Encapsulated Whole-Cell Vaccines Enhance Humoral Immunity against Bacterial Infection - Luzuriaga, Michael A; Herbert, Fabian C; Brohlin, Olivia R; Gadhvi, Jashkaran; Howlett, Thomas; Shahrivarkevishahi, Arezoo; Wijesundara, Yalini H; Venkitapathi, Sundharamani; Veera, Kavya; Ehrman, Ryanne; Benjamin, Candace E; Popal, Sarah; et al. (ACS nano, 2021)
The increasing rate of resistance of bacterial infection against antibiotics requires next generation approaches to fight potential pandemic spread. The development of vaccines against pathogenic bacteria has been difficult owing, in part, to the genetic diversity of bacteria. Hence, there are many potential target antigens and little a priori knowledge of which antigen/s will elicit protective immunity. The painstaking process of selecting appropriate antigens could be avoided with whole-cell bacteria; however, whole-cell formulations typically fail to produce long-term and durable immune responses. These complications are one reason why no vaccine against any type of pathogenic E. coli has been successfully clinically translated. As a proof of principle, we demonstrate a method to enhance the immunogenicity of a model pathogenic E. coli strain by forming a slow releasing depot. The E. coli strain CFT073 was biomimetically mineralized within a metal–organic framework (MOF). This process encapsulates the bacteria within 30 min in water and at ambient temperatures. Vaccination with this formulation substantially enhances antibody production and results in significantly enhanced survival in a mouse model of bacteremia compared to standard inactivated formulations.